2015
DOI: 10.1002/ange.201410773
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Imide Synergy with 3d Transition‐Metal Nitrides Leading to Unprecedented Catalytic Activities for Ammonia Decomposition

Abstract: Alkali metals have been widely employed as catalyst promoters; however, the promoting mechanism remains essentially unclear. Li, when in the imide form, is shown to synergize with 3d transition metals or their nitrides TM(N) spreading from Ti to Cu, leading to universal and unprecedentedly high catalytic activities in NH 3 decomposition, among which Li 2 NH À MnN has an activity superior to that of the highly active Ru/carbon nanotube catalyst. The catalysis is fulfilled via the two-step cycle comprising: 1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
0
39
0
3
Order By: Relevance
“…[260][261][262][263][264] Decomposition of ammonia is a mildly endothermic process, yielding hydrogen and nitrogen (Equation 39). 271 Li 2 NH-MnN was superior to the highly active 5 wt % Ru/CNTs. 271 Alkali metal amides also significantly enhanced catalytic activities of MnN for ammonia decomposition in the order LiNH 2 -MnN > KNH 2 -MnN R NaNH 2 -MnN, which is distinctly different from that of the conventional alkali oxide or hydroxide promoters.…”
Section: Direct Methanol Fuel Cellmentioning
confidence: 92%
“…[260][261][262][263][264] Decomposition of ammonia is a mildly endothermic process, yielding hydrogen and nitrogen (Equation 39). 271 Li 2 NH-MnN was superior to the highly active 5 wt % Ru/CNTs. 271 Alkali metal amides also significantly enhanced catalytic activities of MnN for ammonia decomposition in the order LiNH 2 -MnN > KNH 2 -MnN R NaNH 2 -MnN, which is distinctly different from that of the conventional alkali oxide or hydroxide promoters.…”
Section: Direct Methanol Fuel Cellmentioning
confidence: 92%
“…However, the Ru/CNT catalyst reportedly showed ammonia conversions lower than 50% at 450 °C under a GHSV of 30,000 mL•h −1 •gcat −1 [36,37]. In addition, compared with most of the other reported ammonia decomposition catalysts under similar reaction conditions [22][23][24][25][26], this CS-60 Ru/graphene also showed very attractive catalytic performance for COx-free hydrogen production from ammonia, which indicated that graphene nanosheets supporting Ru nanoparticles is a very productive ammonia decomposition catalyst for practical applications. Figure 6 shows the catalytic performance of Ru/graphene nanocomposites with different levels of Ru loading for ammonia decomposition under a GHSV of 20,000 mL·h −1 ·g cat −1 .…”
Section: Preparation Of Ru/graphene Nanocompositesmentioning
confidence: 93%
“…In this regard, the development of high-performance ammonia decomposition catalysts would be of significant importance for an ammonia-mediated hydrogen economy. Although research effort focused on the catalysis of ammonia decomposition has increased rapidly in recent years [21][22][23][24][25][26][27][28][29][30], and the catalytic activity of current catalysts still requires significant improvement because the current level of ammonia conversion remains much lower than the equilibrium, particularly at reaction temperatures lower than 400 • C. Research progress has identified that Ru is currently the most active component for ammonia decomposition. The control of Ru particles with optimal size and morphology is very important in ammonia decomposition since ammonia decomposition with Ru is structure-sensitive due to the variation of highly active B 5 -type sites [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we developed a composite catalyst system of Li 2 NH-3 d transition metal or transition metal nitride (TM(N)), in which Li 2 NH synergized with 3 d TM(N) (from Ti to Cu) leading to universal high catalytic activities towards NH 3 decomposition [54,55] . In addition to 3 d metals, Ru was also found to synergize with amides and imides of alkali and alkaline earth metals, such as LiNH 2 /Li 2 NH, Ca(NH 2 ) 2 and Ba(NH 2 ) 2 , and these composites exhibited remarkably high activities towards ammonia decomposition [56][57][58] .…”
Section: Thermocatalytic Ammonia Synthesismentioning
confidence: 99%